MIST or INSURE in Preterm Infants with Respiratory Distress Syndrome - Sayed, Marwa Kamel Mohammed; Hassanien, Farouk Elsayed; Khalaf, Mostafa Shafeek; Badawy, Ahlam Badawy Ali (Journal of Child Science, 2024)
Premature infants with respiratory distress syndrome (RDS) are typically administered surfactant via the intubation and extubation procedure (INSURE). A variety of surfactant administration practices are available today. The term “SURE” (surfactant without endotracheal intubation) refers to any approach that requires direct laryngoscopy but uses a narrow catheter instead of an endotracheal tube. They include Take Care, LISA (least invasive surfactant administration), and MIST (minimally invasive surfactant therapy). MIST approaches avoid intubation while minimizing airway damage and barotrauma. This study sought to determine the practicality, effectiveness, and security of using the MIST approach to administer surfactant to premature infants with RDS. The study examined 90 preterm infants who were born before 36 weeks with respiratory distress and were able to breathe on their own. They were divided into two groups of 45 infants each: the MIST and INSURE groups. Both surfactant administration procedures were tested to determine their impact on morbidity and mortality in newborns. The study revealed no noticeable differences between both groups in maternal or newborn factors. Still, the MIST group exhibited a significantly decreasing necessity of mechanical ventilation (MV), had shorter MV and continuous positive airway pressure durations, and significantly reduced periventricular–intraventricular hemorrhage (PIVH) and death. The MIST procedure is pragmatic and reliable, and it decreases the need for MV and mortality in preterm infants who need surfactant treatment. It decreases the occurrence of PIVH in susceptible subgroups.
Keywords: bronchopulmonary dysplasia; minimally invasive surfactant therapy; respiratory distress syndrome; surfactant; preterm